MANAJEMEN KOMUNIKASI PEMERINTAH DESA KOPO KABUPATEN BOGOR DALAM MENDORONG WARGA MELAKUKAN VAKSINASI COVID 19 - Sriwartini, Yayu; Radjagukguk, Djudjur Luciana (JSSHA ADPERTISI JOURNAL, 2023)
This study aimed to describe the communication management of the Kopo Village Government, Bogor Regency, in encouraging residents to vaccinate during a pandemic. Data collection was carried out in August 2022, at which time the government was still promoting the vaccination program. But the problem was many people feel that they no longer need to be vaccinated because apart from the fact that conditions were starting to look normal, people also think that the symptoms of Covid were no longer scary. The data was collected by means of in-depth interviews with informants including the village head, as well as the task force team represented by the head of the Kopo Village PKK and the head of RW 01. The technique of testing the validity of the data was an effort to triangulate sources. In encouraging residents to do vaccines, the Kopo Village Government together with the task force team carried out communication management including preparing messages and ways of communicating, utilizing network-based media such as WAG to disseminate vaccine schedule information and in implementing it carried out persuasive communication through the door prize program and carried out monitoring and evaluation to see the target achievement. Based on the results of the research and discussion, it could be concluded that the Kopo Village Government had carried out quite good communication management in encouraging residents to vaccinate, even though the planning and organizing stages were still not optimal